PENGARUH LIDOCAIN 1,5 mg/Kg BB INTRAVENA TERHADAP TEKANAN DARAH PADA TINDAKAN INTUBASI DI INSTALASI BEDAH SENTRAL RSUD Dr.ISKAK TULUNGAGUNG - Nanang Sugiarto; Yenny Puspitasari; Sugiyanto Sugiyanto (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Intubation is a method to release and defend the respiratory track that can cause a stimulus to the sympathetic nerves in evoking cardiovascular response. Lidocaine is a local anesthesia that can be used to cardiac arrhythmias if it is given intravenously. The purpose of this study is to know the effect of given lidocaine 1,5 mg/Kg BB intravenous to the blood pressure on endotrachea intubation action at Central Surgical Installation at RSUD Dr. Iskak Tulungagung. The research of this study is pre-post test design with control group design. The population is all of male and female patients that undergo surgery or planned surgery with general anesthesia and endotrachea intubation at Central Surgical Installation at RSUD Dr. Iskak Tulungagung. The sample of this study is 32 respondents which are taken by using purposive sampling. Meanwhile, the independent variable is lidocaine and the dependent variable is blood pressure. The data collection uses blood pressure observation sheet before and after intubation without using lidocaine. The data analysis of this study uses the t-two independent α <0.05 statistical test. The result of this study shows that based on 32 respondents, the blood pressure before and after intubation of the intervention group and control group after carried out the t-two independent statistical test indicates that the systole pressure and diastole p value = 0.000 <0.05. It means that there is effect of given lidocaine 1,5 mg/Kg BB before intravenous intubation to the blood pressure. Based on the result of this study, lidocaine before intubation action can be affect to the blood pressure which is caused analgesic effect of the lidocaine itself.